Foreign capital destinations: Baltic States versus India - Tvaronavičienė, Manuela; Grybaitė, Virginija; Korsakienė, Renata (Journal of Business Economics and Management, 2008)
The presented paper aims to elaborate which factors have the biggest influence on investment decisions while choosing between India and the new EU members ‐ Lithuania, Latvia and Estonia. For analysis purpose the Baltic States have been juxtaposed to India, as the latter represents emerging market, and, according to almost unanimous prognosis, is one of the main FDI destinations for the nearest future. The Baltic States are considered as attractive recent entrants of the EU demonstrating high growth and representing new unsaturated market. FDI inflows into those rather different countries started in approximately 1991, thus driving forces behind international capital movement serve as object of scientific interest. The data retrieved and used for considerations embraces period from 1999 to 2008. Authors ground premises about significance of certain sets of driving factors and use multi‐criteria evaluation methods to indicate driving forces determining propensity to invest into the Baltic States’ region and India. Results of speculative analysis are supposed to add to better understanding of contemporary investment behaviour of well‐developed economies.First published online: 14 Oct 2010